Group B streptococcus colonization in pregnancy and neonatal outcomes: a three-year monocentric retrospective study during and after the COVID-19 pandemic - Gregorio Serra; Lucia Lo Scalzo; Maria Giordano; Mario Giuffrè; Pietro Trupiano; Renato Venezia; Giovanni Corsello (BMC, 2024)
Abstract Background Group B Streptococcus (GBS) is a major cause of sepsis and meningitis in newborns. The Centers for Disease Control and Prevention (CDC) recommends to pregnant women, between 35 and 37 weeks of gestation, universal vaginal-rectal screening for GBS colonization, aimed at intrapartum antibiotic prophylaxis (IAP). The latter is the only currently available and highly effective method against early onset GBS neonatal infections. Since the onset of the coronavirus disease 2019 (COVID-19) pandemic, the preventive measures implemented to mitigate the effects of SARS-CoV-2 infection led to the reduction in the access to many health facilities and services, including the obstetric and perinatal ones. The purpose of the present study was to evaluate the prevalence of maternal GBS colonization, as well as use of IAP and incidence of episodes of neonatal GBS infection when antibiotic prophylaxis has not been carried out in colonized and/or at risk subjects, in a population of pregnant women during (years 2020-2021) and after (year 2022) the COVID-19 pandemic, also with the aim to establish possible epidemiological and clinical differences in the two subjects' groups. Methods We retrospectively analyzed the clinical data of pregnant women admitted to, and delivering, at the Gynaecology and Obstetrics Unit, Department of Sciences for Health Promotion and Mother and Child Care, of the University Hospital of Palermo, Italy, from 01.01.2020 to 31.12.2022. For each of them, we recorded pertinent socio-demographic information, clinical data related to pregnancy, delivery and peripartum, and specifically execution and status of vaginal and rectal swab test for GBS detection, along with eventual administration and modality of IAP. The neonatal outcome was investigated in all cases at risk (positive maternal swabs status for GBS, either vaginal or rectal, with or without/incomplete IAP, preterm labor and/or delivery, premature rupture of membranes ≥ 18 h, previous pregnancy ended with neonatal early onset GBS disease [EOD], urine culture positive for GBS in any trimester of current gestation, intrapartum temperature ≥ 38 °C and/or any clinical/laboratory signs of suspected chorioamnionitis). The data concerning mothers and neonates at risk, observed during the pandemic (years 2020-2021), were compared with those of both subjects' groups with overlapping risk factors recorded in the following period (year 2022). The chi squared test has been applied in order to find out the relationship between pregnant women with GBS colonization receiving IAP and outcome of their neonates. Results The total source population of the study consisted of 2109 pregnant women, in addition to their 2144 newborns. Our analysis, however, focused on women and neonates with risk factors. The vaginal-rectal swab for GBS was performed in 1559 (73.92%) individuals. The test resulted positive in 178 cases overall (11.42% of those undergoing the screening). Amongst our whole sample of 2109 subjects, 298 women had an indication for IAP (vaginal and/or rectal GBS colonization, previous pregnancy ended with neonatal GBS EOD, urine culture positive for GBS in any trimester of current gestation, and unknown GBS status at labor onset with at least any among delivery at < 37 weeks' gestation, amniotic membranes rupture ≥ 18 h and/or intrapartum temperature ≥ 38.0 °C), and 64 (21.48%) received adequate treatment; for 23 (7.72%) it was inadequate/incomplete, while 211 (70.8%) did not receive IAP despite maternal GBS colonization and/or the presence of any of the above mentioned risk factors. Comparing the frequency of performing vaginal-rectal swabs in the women admitted in the two time periods, the quote of those screened out of the total in the pandemic period (years 2020-2021) was higher than that of those undergoing GBS screening out of the total admitted in the year 2022 (75.65% vs. 70.38%, p = 0.009), while a greater number (not statistically significant, p = 0.12) of adequate and complete IAP was conducted in 2022, than in the previous biennium (26.36 vs. 18.62%). During the whole 3 years study period, as expected, none of the newborns of mothers with GBS colonization and/or risk factors receiving IAP developed EOD. Conversely, 13 neonates with EOD, out of 179 (7.3%) born to mothers with risk factors, were observed: 3 among these patients' mothers performed incomplete IAP, while the other 10 did not receive IAP. Neither cases of neonatal meningitis, nor deaths were observed. The incidence rate in the full triennium under investigation, estimated as the ratio between the number of babies developing the disease out of the total of 2144 newborns, was 6.06‰; among those born to mothers with risk factors, if comparing the two time periods, the incidence was 8.06% in the pandemic biennium, while 5.45% in the following year, evidencing thus no statistical significance (p = 0.53). Conclusions The present study revealed in our Department an increased prevalence of pregnant women screened for, and colonized by GBS, in the last decade. However, an overall still low frequency of vaginal-rectal swabs performed for GBS, and low number of adequate and complete IAP despite the presence of risk factors have been found, which did not notably change during the two time periods. Moreover, significant EOD incidence rates have been reported among children of mothers carrying risk factors, although also in this case no statistically significant differences have been observed during and after the pandemic. Such data seem to be in contrast to those reported during the COVID-19, showing a decrease in the access to health facilities and increased mortality/morbidity rates also due to the restrictive measures adopted to mitigate the effects of the pandemic. These findings might be explained by the presence within the same metropolitan area of our Department of a COVID hospital and birthing center, which all the patients with SARS-CoV-2 infection referred to, and likely leading to a weaker concern of getting sick perceived by our patients. Although IAP is an easy procedure to implement, however adherence and uniformity in the management protocols are still not optimal. Therefore, the prophylactic measures adopted to date cannot be considered fully satisfactory, and should be improved. Better skills integration and obstetrical-neonatological collaboration, in addition to new effective preventive tools, like vaccines able to prevent invasive disease, may allow further reduction in morbidity and mortality rates related to GBS perinatal infection.